Internet connectivity disruption in Turkey (Turkey) - Voidly (2026)
CRITICAL severity mixed detected in Turkey. Confidence: 75%. Data sourced from IODA, CensoredPlanet.
Censorship Incident ID: TR-2026-0064
Keywords: censorship; TR; mixed; critical